2010
DOI: 10.1158/0008-5472.can-09-3619
|View full text |Cite
|
Sign up to set email alerts
|

CD44posCD49fhiCD133/2hi Defines Xenograft-Initiating Cells in Estrogen Receptor–Negative Breast Cancer

Abstract: Defining the populations of tumor-initating cells that are present in tumors is a first step in developing therapeutics to target these cells. We show here that both CD44posCD24neg and CD44posCD24pos cell populations in estrogen receptor (ER) α–negative breast tumors are tumorigenic in murine xenograft models. We also describe a third population of xenograft-initiating cells (XIC) enriched in CD44posCD49fhiCD133/2hi cells that display heightened tumorigenicity, self-renewal in vivo, and the capacity to give ri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(112 citation statements)
references
References 46 publications
(58 reference statements)
5
107
0
Order By: Relevance
“…This may be difficult because of the low proportion of such cells in a cancer. On the other hand, the joint use of several biomarkers on histological preparations could indicate in vivo colocalization or its absence (see, for example, CSC-TPC markers (Meyer et al, 2010;Roesch et al, 2010). As EMT is a reversible process, EMT cells included in the CSC-TPC populations would thus constitute within this population a reversible phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be difficult because of the low proportion of such cells in a cancer. On the other hand, the joint use of several biomarkers on histological preparations could indicate in vivo colocalization or its absence (see, for example, CSC-TPC markers (Meyer et al, 2010;Roesch et al, 2010). As EMT is a reversible process, EMT cells included in the CSC-TPC populations would thus constitute within this population a reversible phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…A similar absence of overlap between 'CSC' markers has been observed in colon cancer cells . Similarly, when three biomarkers (CD44, CD24, CD133 and so on) are used to stain human breast cancer cells as CSC-TPC, each biomarker labels a largely different cell population (Meyer et al, 2010). However, the cells expressing the three biomarkers are the most efficient for xenotransplant or tumorosphere growth and express embryonic stem cell (ESC) biomarkers.…”
Section: Csc-tpc Biomarkersmentioning
confidence: 99%
“…Xenograft-initiating breast cancer cells enriched in CD44 + /CD49f high / CD133/2 high cells were also shown to have elevated expression of Nanog homeobox (NANOG), SRY-box 2, and polycomb complex protein BMI-1 (73). Further extensive CD133 profiling in breast cancer needs to be performed to confirm CD133 + breast cancer cells as tumor-initiating cells.…”
Section: Cd133 (Prominin-1)mentioning
confidence: 99%
“…24 Xenograft-initiating BC cells enriched in CD44 pos CD49f hi CD133/2 hi cells also show unlimited selfrenewal capabilities. 25 Other studies have observed that CD44 and CD133 are over-expressed in mammospheres derived from BC tissues and cell lines. 26,27 In addition to being a stem cell-related marker; other properties such as cellular migration by facilitating EMT [28][29][30] and vasculogenic mimicry (VM) 31 have been linked to CD133 1 cells.…”
mentioning
confidence: 95%